Organizational and Legal Principles of Soviet Militia Dispatch Center’s Functioning during 1969–1991 - D. V. Halkin; O. M. Halkina (Bulletin of Kharkiv National University of Internal Affairs)
The normative and legal provision, organization and activity of militia dispatch centers of Soviet Ukraine in 1969–1991 have been studied.